The Correlation Of Sex And Exclusive Breastfeeding Status With Acute Respiratory Infection (Ari) Incidence Among Under-Five Children At The Cempaka Public Health Center Banjarmasin - Nurul Hidayah; M. Rasyid Ridha Ramadhan (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Acute Respiratory Infection (ARI) has the first cause of death in infants and toddlers in Indonesia. Based on National Health Survey data shows that the proportion of ARI as a cause of infant mortality is 27.6%, whereas ARI as the cause of death of children under five is 22,8%. Currently, ARI disease is still a health problem that needs attention and needs to be immediately overcome. ISPA is a disease whose risk may increase due to sex and exclusive breastfeeding status.Purpose: The purpose of this study is to know the correlation between sex and exclusive breastfeeding status with the incidence of acute respiratory infections among children under five at the Cempaka Public Health Center Banjarmasin.Method: This research was an analytic survey research using cross-sectional study approach. The samples of this study were all children under five years old who visited Cempaka Public health Center on the 3rd week of July - 1st week of August taken by accidental sampling technique amounted to 50 people.Result: Most of the respondents were male as many as 32 toddlers (64%), exclusive breastfeeding status was mostly not exclusive breastfeeding (64%), and most respondents had ARI for 31 toddlers (62%). The statistic test result of sex correlation with the incidence of ARI was obtained p-value = 0.026 and OR = 4.714 (95% CI: OR = 1.364-16.295). While the statistical test result of exclusive breastfeeding status correlation with the incidence of ARI obtained p-value = 0.000 and OR = 18.900 (95% CI: OR = 4.369-81.765).Conclusion: In this study proved that there is a significant relationship between sex and exclusive breastfeeding status with the incidence of ARI among under-five children.Keywords: Acute Respiratory Infection (ARI), Children under-five, Exclusive breastfeeding status, Sex